Impact of COVID-19 on pregnant women in South Korea: Focusing on prevalence, severity, and clinical outcomes - So Hee Kim; Yeonmi Choi; Dokyoung Lee; Hyejin Lee; Ji Hoi Kim; Eun Saem Choi; Young Mi Jung; Jinwoo Lee; Pyoeng Gyun Choe; Ji Yoon Lee; Youngme Do; Chan-Wook Park; et al. (Elsevier, 2022)
Background: In the era of coronavirus disease 2019 (COVID-19) pandemic, there is a paucity of information regarding actual prevalence of COVID-19 in pregnant women compared to non-pregnant women. The purpose of this study was to investigate the prevalence of COVID-19 infection and clinical outcome in pregnant women and non-pregnant women. Methods: This is a nationwide cross-sectional study in South Korea between January 2020 and February 2021 using the claim database. The primary outcome was the prevalence of COVID-19 in pregnant women, and the secondary outcome was the occurrence of severe COVID-19 illness among infected patients. Severity of COVID-19 was classified into four categories according to WHO ordinal scale. Results: The prevalence of COVID-19 infection was lower in pregnant women than non-pregnant women aged 20-44 (0·02% vs. 0.14%, p < 0.0001). However, among COVID-19 positive women at age 20-44, pregnant women was at higher risk of oxygen therapy after hospitalization (score 4 in WHO ordinal scale: 6.4% vs. 1.6%, p < 0.05). There were no deaths or hospitalized severe disease in pregnant women with COVID-19, although the majority of them (96·2%) were admitted to hospital. On the other hand, 42·3% of non-pregnant women at 20-44 age were admitted to hospital and 0.04% of them died and 0.1% had hospitalized severe disease. Conclusions: The prevalence of COVID-19 infection in pregnant women was lower than non-pregnant women in Korea, resulting in relatively small cases of fatality. It has implications that public health policy, such as an effective response to COVID-19 and a powerful preemptive strategy for pregnant women, can lower risk of COVID-19 infection and better clinical outcomes in pregnant women with COVID-19.